2020
DOI: 10.1038/s41420-020-00312-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-3148 acts as molecular switch promoting malignant transformation and adipocytic differentiation of immortalized human bone marrow stromal cells via direct targeting of the SMAD2/TGFβ pathway

Abstract: MicroRNAs (miRs/miRNAs) play a key role in posttranscriptional regulation of gene expression and are implicated in a number of physiological and pathological conditions, including cellular malignant transformation. In the current study, we investigated the role of miR-3148 in regulating human stromal (mesenchymal) stem cell (hMSC) differentiation and transformation. Stable expression of miR-3148 in telomerized hMSC (hMSC-miR-3148) led to significant increase in in vitro adipocytic differentiation and suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The Acridine orange/ethidium bromide (AO/EtBr) fluorescence staining method was used to assess apoptosis/necrosis in TNBC cells, as we described before [ 17 ]. On day 5 post siRNA transfection, TNBC cells were washed twice with PBS and were then stained with dual fluorescent staining solution (100 μg/mL AO and 100 μg/mL EtBr (AO/EtBr, Sigma Aldrich, St. Louis, MO, USA)) for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…The Acridine orange/ethidium bromide (AO/EtBr) fluorescence staining method was used to assess apoptosis/necrosis in TNBC cells, as we described before [ 17 ]. On day 5 post siRNA transfection, TNBC cells were washed twice with PBS and were then stained with dual fluorescent staining solution (100 μg/mL AO and 100 μg/mL EtBr (AO/EtBr, Sigma Aldrich, St. Louis, MO, USA)) for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“… 35 Vishnubalaji et al, demonstrated that miR-3148 acted as molecular switch promoting malignant transformation and adipocytic differentiation of immortalized human bone marrow stromal cells via direct targeting of the SMAD2/TGFβ pathway. 36 Collectively, the above evidence indicated that miR-3148 acted as onco-miRNA in CRC by repressing OTOP2 expression. However, as we have not examined the expression of miR-3148 in the CRC tissues, and whether miR-3148 expression was inversely correlated with OTOP2 expression in CRC tissues remains to be clarified.…”
Section: Discussionmentioning
confidence: 89%